2012
DOI: 10.1590/s0100-67622012000500002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo nutricional da canafístula (II): eficiência nutricional em função da adubação com nitrogênio e fósforo

Abstract: RESUMO -Objetivou-se, neste trabalho, avaliar o efeito de doses combinadas de N e P no conteúdo de nutrientes, bem como na eficiência nutricional de mudas de canafístula (Peltophorum dubium Spreng. Taub.), em Latossolo Vermelho distroférrico. O experimento foi desenvolvido em vasos de 4 dm 3 , com os tratamentos dispostos em fatorial 4x4, sendo quatro doses de N -fonte ureia (0; 20,82; 41,64; e 62,46 mg kg -1 de N) e quatro doses de P -fonte superfosfato triplo (0; 41,72; 83,72; e 125,16 mg kg -1 de P 2 O 5 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…This variable expresses the capacity by which the seedlings have to use existing resources to produce higher rates of photosynthesis and biomass. Souza et al (2012), conducting a nutritional study on canafistula, concluded that the species has a high requirement of the nitrogen from chemical fertilizers. The organic substrates tested in this experiment, especially poultry manure (Table 1), are rich in nitrogen and, thus, have supplied the nutritional needs of canafistula.…”
Section: Discussionmentioning
confidence: 99%
“…This variable expresses the capacity by which the seedlings have to use existing resources to produce higher rates of photosynthesis and biomass. Souza et al (2012), conducting a nutritional study on canafistula, concluded that the species has a high requirement of the nitrogen from chemical fertilizers. The organic substrates tested in this experiment, especially poultry manure (Table 1), are rich in nitrogen and, thus, have supplied the nutritional needs of canafistula.…”
Section: Discussionmentioning
confidence: 99%
“…According to Souza et al (2012) the Cerrado soil is composed of about 46% of latosol. Latosol is characterized by a low availability of nutrients, acid reaction, low cation exchange capacity and low organic matter content, which among other features, lead to a poor absorption of nutrients by plants, especially nitrogen (N) and phosphorus (P).…”
Section: Discussionmentioning
confidence: 99%
“…No studies were found to evaluate species in the natural regeneration phase. Young individuals (seedlings) are usually evaluated in experiments in a protected and controlled environment, with the objective of studying the BUE of nutrients in response to the fertilization of a certain nutrient, such as the studies developed by N. Souza et al (2012) and N. Carnevali, Marchetti, Vieira, T. Carnevali, and Ramos (2016).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of nutritional aspects of native species is important in order to understand the establishment of these species in their origin sites, especially in areas with low nutrient availability soils, such as tropical soils (N. Souza et al, 2012). This information, when obtained specifically for natural regeneration species, which are in the initial phase of its development (Felfili, Rezende, Silva-Júnior, & M. A. Silva, 2010), combined with the knowledge of these species' autecology (Schorn & Galvã o, 2006) may subsidize the indication for use in reforestation.…”
Section: Introductionmentioning
confidence: 99%